Waqf as Alternative Financing Resource for Infrastructure Development in Indonesia: Analytical Hierarchy Process Approach - Muhammad Faiz Andeaz Fawwaz; Juliana Juliana; Aneu Cakhyaneu; Mumuh Muhammad; Ropi Marlina (Islamic Research, 2020)
The productive Waqf can be utilized for developing infrastructure in Indonesia as this country has incredible waqf potential. However, the utilization of waqf assets has not been specified for infrastructure development, which has many benefits (maslahah) for Indonesia. This study aims to determine the main problem in utilizing Waqf for infrastructure development in Indonesia from regulatory dimension, management dimension, program dimension, and literacy dimension. The data analysis technique used in this study is Analytical Hierarchy Process (AHP). This study has five experts to deliver their perspective regarding problems and solutions for infrastructure development using productive Waqf in Indonesia. The study results indicate that the severe problem in utilizing productive Waqf for infrastructure in Indonesia based on experts' agreement is the Lack of professional waqf (nazhir) management in managing waqf assets. With increasing the professionalism of nazhir in the management of productive Waqf, the waqf assets are expected to grow gradually that can be used to develop and improve infrastructure in Indonesia. Lastly, the excellent management of Waqf will be able to attract the Muslim community's intention to donate.